2011
DOI: 10.1007/s00726-011-0889-z
|View full text |Cite
|
Sign up to set email alerts
|

Using predicted shape string to enhance the accuracy of γ-turn prediction

Abstract: Numerous methods for predicting γ-turns in proteins have been developed. However, the results they generally provided are not very good, with a Matthews correlation coefficient (MCC)≤0.18. Here, an attempt has been made to develop a method to improve the accuracy of γ-turn prediction. First, we employ the geometric mean metric as optimal criterion to evaluate the performance of support vector machine for the highly imbalanced γ-turn dataset. This metric tries to maximize both the sensitivity and the specificit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
12
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 16 publications
(12 citation statements)
references
References 34 publications
0
12
0
Order By: Relevance
“…Many studies have taken advantage of backbone conformational information (44 -46). Our previous work (47,48) demonstrated that backbone string was important for turn identification as well. The second advantage was that the backbone string was more conservative than the sequence.…”
Section: Discussionmentioning
confidence: 99%
“…Many studies have taken advantage of backbone conformational information (44 -46). Our previous work (47,48) demonstrated that backbone string was important for turn identification as well. The second advantage was that the backbone string was more conservative than the sequence.…”
Section: Discussionmentioning
confidence: 99%
“…Shape string is a one-dimensional string of symbols, which can carry more structural information than the classical secondary structure representation [27]. Typically, shape T reflects the turn structure in protein, and predicted shape T could help to identify the turns [16], [17]. The observed shape string can be freely obtained based on a sequence of known structure from the web server [12].…”
Section: Methodsmentioning
confidence: 99%
“…In our previous studies, the predicted shape string was explored as an effective feature to promote the accuracies of predicting a β–turn [16], a γ–turn [17], a unified turn model [18], a DNA-binding residue [19] and a domain boundary [20]. The shape string was also considered as a backbone string to reconstruct the modeling of membrane proteins [21].…”
Section: Introductionmentioning
confidence: 99%
“…γ-turn is the second most characterized tight turn, which involves three amino acid residues and a hydrogen bond between the backbone CO (i) and the backbone NH (i+2) . The problems of γ-turn prediction can be divided into two categories: prediction of γ-turn types [12] and prediction of γ-turn/non-γ-turn [13], [14], [15]. The method proposed by our group [15], which utilized G-means metrics as the optimal criterion for SVM and predicted shape string as a new variable.…”
Section: Introductionmentioning
confidence: 99%
“…The problems of γ-turn prediction can be divided into two categories: prediction of γ-turn types [12] and prediction of γ-turn/non-γ-turn [13], [14], [15]. The method proposed by our group [15], which utilized G-means metrics as the optimal criterion for SVM and predicted shape string as a new variable. α-turn is always present on the exposed surface of the protein and contains specific information for the molecular recognition process.…”
Section: Introductionmentioning
confidence: 99%